Toxicidade do óleo de nim (Azadirachta indica A. JUSS) na espermatogênese de Ceraeochrysa claveru (NAVÁS, 1911)(Neuroptera: Chysopidae): estudo citoquímico, imunocitoquímico e ultraestrutural - Garcia, Ana Silvia Gimenes [UNESP] (2014)
The use of organic agriculture is growing due to the awareness of the society about the importance of eating foods free of pesticides and insecticides as harmful to health. Thus, the search for conservation of natural resources is also growing, along with organic agriculture and integrated pest management. In search of insects that can be used in biological control, which is an important tool in organic agriculture and integrated pest management, the lacewings has proved a strong controlling agent, since their larvae are predators of eggs and larvae of many insects pests of different commercial crops. In order to evaluate the effect of neem oil, a plant extract with insecticides properties on lacewings, Diatraea saccharalis eggs were treated with neem oil at three different concentrations and offered as food for the larvae of Ceraeochrysa claveri, thereby evaluating the effect of intake of neem oil on the larval morphology of testis during development of C. claveri, as well as on the process of spermatogenesis of this predator. Histological, ultrastructural, and immunohistochemistry analysis was used to evaluate the toxicity of neem oil on cells of the testis of C. claveri, and this evaluation performed in testes of third instar larvae, pupae and adults. The analyzes showed that the morphology of the testes varies from rounded shape in larvae to elongated shape in pupae and spiral shape in adults, while its color varies from whitish to bright yellow, respectively. The testes are covered by an outer layer and an inner layer, the latter septa emit, which divide the testis into two follicles. The germ cells are grouped into cysts, cystic surrounded by somatic cells. These cysts consist of spermatogonia, spermatocytes, spermatids and spermatozoa. The spermatogonia undergo mitotic division and give rise to spermatocytes, the cells of the cysts are interconnected by ring canals, which allow their synchronous ...